Ideologi sosial politik pada karya semsar siahaan / Anggiat Tornado - Tornado, Anggiat (Universiti Teknologi MARA, Perak, 2016)
The ideology refers to a system of thinking adopted by the artist in expressing criticism and their mind in the form of the contemporary art work with the subject of two artists: 1) Semsar Siahaan with the work of installation redigging (Kuburan Massal, 1999) said that the history of cruelty in Indonesia especially violation of human rights has been buried with a new history being recreated again. His work's painting works Manubilis (1998); Human, animals and the devil a term describing Manubilis three characteristics in one unity. Man as a body, animals as desires, and the devil as cunning and cheating, and in the his other work shade of Northen Lights (2004). He was suing about inequality and talk about global humanity. The ideology of the two artists refers to the reality of a group that oppressed with structured by a sovereign and investor. I says it as humanist ideology